Organizational commitment of employees as a result of job satisfaction - Ilić-Koderman Đurđijana (Trendovi u Poslovanju)
In modern business conditions, human resources are the most valuable resource that enables the realization and maintenance of the competitive advantage of the organization. Given this statement, it is not surprising why in recent decades in professional and academic circles there is a growing interest in researching issues of how to improve, retain and motivate employees to invest their maximum efforts in achieving organizational goals. As companies are both capital and labor intensive, it is easy to come to the conclusion that depending on the degree of motivation and commitment of employees to the realization of organizational goals, the realization of the above-mentioned imperative also depends on it. In other words, the degree to which employees identify with their organization depends on how motivated they will be to achieve its goals and to participate in improving its efficiency. This means that organizational commitment is becoming one of the key determinants of the success of 21st century organizations. Generally speaking, job satisfaction is an attitude that manifests in the workplace as individual behavior of the employee and can have an impact on the organization and organizational behavior. Job satisfaction encourages employees to increase performance and commitment to the organization, while reducing absenteeism and increasing interest in the profession, and it is of immeasurable importance to pay attention to the cause-and-effect relationship of job satisfaction and organizational commitment.